Chemical Reaction Monitoring using Zero‐Field Nuclear Magnetic Resonance Enables Study of Heterogeneous Samples in Metal Containers. (24th July 2020) - Burueva, Dudari B.; Eills, James; Blanchard, John W.; Garcon, Antoine; Picazo‐Frutos, Román; Kovtunov, Kirill V.; Koptyug, Igor V.; Budker, Dmitry
Abstract: We demonstrate that heterogeneous/biphasic chemical reactions can be monitored with high spectroscopic resolution using zero‐field nuclear magnetic resonance spectroscopy. This is possible because magnetic susceptibility broadening is negligible at ultralow magnetic fields. We show the two‐step hydrogenation of dimethyl acetylenedicarboxylate with para‐enriched hydrogen gas in conventional glass NMR tubes, as well as in a titanium tube. The low frequency zero‐field NMR signals ensure that there is no significant signal attenuation arising from shielding by the electrically conductive sample container. This method paves the way for in situ monitoring of reactions in complex heterogeneous multiphase systems and in reactors made of conductive materials while maintaining resolution and chemical specificity. Abstract : Authority zero : Process monitoring of a hydrogenation reaction using zero‐field NMR spectroscopy is possible if the reaction is performed with H2 gas enriched in the para nuclear spin isomer, which gives hyperpolarized NMR signals. Zero‐field NMR allows the reaction to be monitored through a metal tube during continuous bubbling of hydrogen into solution, while maintaining the specificity of high‐field NMR spectroscopy.